2015
DOI: 10.1111/gcb.13106
|View full text |Cite
|
Sign up to set email alerts
|

Global impacts of the 1980s regime shift

Abstract: Despite evidence from a number of Earth systems that abrupt temporal changes known as regime shifts are important, their nature, scale and mechanisms remain poorly documented and understood. Applying principal component analysis, change‐point analysis and a sequential t‐test analysis of regime shifts to 72 time series, we confirm that the 1980s regime shift represented a major change in the Earth's biophysical systems from the upper atmosphere to the depths of the ocean and from the Arctic to the Antarctic, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
210
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 272 publications
(241 citation statements)
references
References 62 publications
24
210
0
7
Order By: Relevance
“…5). This is an agreement with the abrupt temperature change observed at this date by recent studies Brulebois et al, 2015;Reid et al, 2016) which for the west part of Europe correspond to the 'start' of the surface warming. Similar results are observed when frost stress is derived from station or gridded climate data (Tab.…”
Section: Evolution Of the Frost Stresssupporting
confidence: 92%
See 2 more Smart Citations
“…5). This is an agreement with the abrupt temperature change observed at this date by recent studies Brulebois et al, 2015;Reid et al, 2016) which for the west part of Europe correspond to the 'start' of the surface warming. Similar results are observed when frost stress is derived from station or gridded climate data (Tab.…”
Section: Evolution Of the Frost Stresssupporting
confidence: 92%
“…These results support recent works Brulebois et al, 2015) conducted over Burgundy and France as well as over Europe (Reid et al, 2016) and global scale (Reid and Beaugrand, 2012;Xiao et al, 2012) that show an abrupt warming in 1987/1988. Our results show a higher warming for T max than for T min .…”
Section: Temperatures Interpolationsupporting
confidence: 91%
See 1 more Smart Citation
“…Low AR-1 values (far from the theoretical value of 1 at which critical transitions occur) reflect the fact that transitions in the real world are likely triggered well before the actual tipping point is reached (25,39). Evaluation of the full power spectrum for changes in power in aggregated low vs. high frequencies over time indicated that higher-order AR processes did not provide more information than the AR-1.…”
Section: Discussionmentioning
confidence: 93%
“…This change is explained by a northward expansion of the Hadley cell, a poleward expansion and intensification of the Ferrel cell, and a collapse of the polar cell (Kim et al, 2015). A thorough analysis of the regime shifts in the 1980s and their global impact on the biosphere was conducted by Reid et al (2016).…”
Section: Introductionmentioning
confidence: 99%